Strategi Coping Mahasiswa dalam Menghadapi Kurangnya Perhatian Orang Tua: Studi Kasus Mahasiswa Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Palopo - Said, A.Nurdin; Marhani; Zainuri, Muhammad Irham (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Lack of parental attention is a psychosocial issue that can significantly affect students' emotional well-being, especially during early adulthood. This study aims to explore the coping strategies used by students of the Guidance and Counseling Study Program at Universitas Muhammadiyah Palopo in dealing with the lack of parental attention. This research employs a qualitative approach using a case study method, involving three main informants who meet the criteria of experiencing insufficient parental attention. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the coping strategies used by the students fall into two main categories: emotion-focused coping and problem-focused coping. Emotion-focused strategies include seeking emotional support from peers, engaging in religious activities such as prayer, and participating in enjoyable activities to release emotional tension. Meanwhile, problem-focused coping is evident in students' efforts to stay academically focused, establish positive routines, and foster independence. These strategies serve to alleviate psychological stress due to the lack of parental attention and support students in maintaining mental stability and academic functioning. The study also highlights the importance of social support and spiritual approaches as effective coping resources in the student context.